Biostable highly aligned polyurethane fibres for the potential application of small calibre vascular grafting. Issue 11 (10th November 2020) - Tan, C.J.; Ang, B.C.; Andriyana, A.; Chagnon, G.
Abstract: Synthetic vascular grafting is necessarily when the autografting is not possible in some cases. Conventional polyethylene terephthalate and expanded polytetrafluoroethylene vascular grafts are found to be effective for diameter bigger than 6 mm but not for the diameter smaller than 4 mm due to the compliance mismatch and thrombogenicity. Endothelization on the surface of the graft can reduce the risks of compliance mismatch and thrombogenicity. In order to catalyst the endothelization process, fibrous morphology similar to the extracellular matrix of our body is preferable in the vascular grafts. Apart from that, the biostability of the grafts is also an essential element to be considered as the biodegradation may reduce the efficiency of the grafts. Many polyurethanes have been recognised as biostable materials. Hence, in this study, highly aligned polyurethane fibres are fabricated using a facile dry spinning technique in the view of providing effective sites for endothelization process to occur. These fibres are immersed into the simulated body fluid for as long as 24 weeks before conducting the biostability characterisations. The biostability is assessed in three aspects, physical, mechanical and chemical properties. Results show that the fibres do not have observable or significant deteriorations in all the three aspects mentioned. Abstract : The biostability of dry spun highly aligned polyurethane fibres is assessed in terms of physical, mechanical and chemical properties for the potential application of small calibre vascular grafting. Results show that the fibres do not show obvious deterioration in all the three properties even after 24 weeks of immersion in simulated body fluid.